2001
DOI: 10.1007/pl00000834
|View full text |Cite
|
Sign up to set email alerts
|

The surface glycopeptidolipids of mycobacteria: structures and biological properties

Abstract: One of the most important opportunistic pathogens associated with acquired immunodeficiency syndrome (AIDS) is the M. avium complex. M. avium infections are found in up to 70% of individuals in advanced stages of AIDS. It is apparent that M. avium can replicate in host macrophages and persist for long periods. This group of mycobacteria are distinguished by the presence of unique, highly antigenic, surface-located lipids known as the glycopeptidolipids (GPLs). The GPLs are the chemical basis of the 31 distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 127 publications
(104 reference statements)
1
153
0
Order By: Relevance
“…These simplest forms are found in all GPL-containing mycobacterial species and, accordingly, are called non-servar-specific GPLs or apolar GPLs. The allo-threoninyl-linked sugar unit of non-servar-specific GPLs may be further glycosylated in some GPL-containing mycobacteria, such as M. avium (33,34). These discrete modifications confer to GPLs variable TLC patterns and antigenic properties (20,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…These simplest forms are found in all GPL-containing mycobacterial species and, accordingly, are called non-servar-specific GPLs or apolar GPLs. The allo-threoninyl-linked sugar unit of non-servar-specific GPLs may be further glycosylated in some GPL-containing mycobacteria, such as M. avium (33,34). These discrete modifications confer to GPLs variable TLC patterns and antigenic properties (20,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…et al, 1983). Studies have shown that GPLs of M. avium are immunosuppressive and induce some cytokines, thus affecting the host's response to infection (Chatterjee & Khoo, 2001 ;Horgen et al, 2000). Most mycobacterial Abbreviations : DIG, digoxigenin ; ESI-MS, electrospray ionization mass spectrometry ; GPL, glycopeptidolipid ; HPTLC, high-performance thin-layer chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…However, GPLs of serotype 10 and 11 have been shown to be identical by GC-MS and ELISA . Another distinct characteristic of the ssGPLs that is shared by all three PCR-negative M. avium serotypes is a unique component that allows attachment of haptenic oligosaccharide to the N-acylpeptide core (Chatterjee & Khoo, 2001). We suggest that the lack of genes used as markers in the present study reflects an altered genetic basis for the ssGPL biosynthesis in these strains.…”
Section: Dna Amplification Gene Sequences and Alignmentmentioning
confidence: 81%
“…With the exception of serotypes 5, 10 and 11, which are distinguished by the 3-O-Mea-L-Rhap-(1R2)-dTal component, this unit is present in all serotypes, serving as a core to which the next sugar is added during oligosaccharide chain elongation (Chatterjee & Khoo, 2001). Insertional inactivation by a mobile element or deletion of the gene responsible for the addition of that sugar would lead to the formation of the serotype 1 GPL, regardless of the presence of genes encoding enzymes necessary for further modification of the GPL.…”
Section: Phylogenymentioning
confidence: 99%
See 1 more Smart Citation